2021
DOI: 10.3389/fmed.2021.778129
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Antibodies Against Spike Glycoprotein of SARS-CoV-2 in Healthcare Workers Post Double Dose of BBV-152 and AZD1222 Vaccines

Abstract: Purpose: We investigated the persistence of the vaccine-induced immunoglobulin G (IgG) antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) among healthcare workers (HCWs) in Odisha who received a complete dose of either Covaxin or Covishield vaccine.Methods: This 24-week longitudinal cohort study was conducted from January to July 2021 with participants from 6 healthcare and research facilities of Odisha to understand the dynamicity of the vaccine-induced IgG antibodies against SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 17 publications
3
24
1
Order By: Relevance
“…However, in Covaxin recipients anti-spike antibody GMT was relatively stable over the 6-months with minimal-to-no (8%) decline despite a modest rise in anti-spike GMT at all time points. Our finding is in contrary to the only other longitudinal study of Covaxin in Indian HCWs that found a 4-fold decrease in median anti-spike antibody titer at 6-month whilst Covishield recipient had only 2-fold decline despite a significantly higher median antibody titer with Covishield at all time points vs. Covaxin [ 11 ]. As mentioned earlier, other Indian study reported a 72% decay rate in antibody titre at 6-month in Covishield recipient [ 10 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, in Covaxin recipients anti-spike antibody GMT was relatively stable over the 6-months with minimal-to-no (8%) decline despite a modest rise in anti-spike GMT at all time points. Our finding is in contrary to the only other longitudinal study of Covaxin in Indian HCWs that found a 4-fold decrease in median anti-spike antibody titer at 6-month whilst Covishield recipient had only 2-fold decline despite a significantly higher median antibody titer with Covishield at all time points vs. Covaxin [ 11 ]. As mentioned earlier, other Indian study reported a 72% decay rate in antibody titre at 6-month in Covishield recipient [ 10 ].…”
Section: Discussioncontrasting
confidence: 99%
“…From the Indian vaccine study standpoint, a prospective longitudinal study from India involving 122 HCWs found a substantial decline in levels of anti-spike antibody (S1 subunit) at 6-month compared to the peak values (one month) after the second dose of the Covishield vaccine, suggesting a sharper decay rate of 72% [ 10 ]. Another longitudinal cohort study involving 533 HCWs that compared humoral response in both Covishield and Covaxin recipients found a 2- and 4-fold decrease in anti-spike antibody titer respectively, at 6 months, when measured as median value (95% IQR) [ 11 ]. Contrarily, few other studies showed different results with other vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate that BCG does not significantly alter the published kinetics of spikespecific Ab and T cell responses induced by the COVISHIELD TM vaccine in a seronegative population, with Ab binding and NAb levels peaking 3 weeks post prime (as recorded in Fig. 2) and further enhanced at 2 weeks post boost [51][52][53][54][55][58][59][60] , a time point that we were unable to collect. However, we show a clear boost to Ab binding and NAb levels at 5-6 weeks, implying the booster dose effect is sustained up to 5-6 weeks before waning.…”
Section: Bcg Revaccination Enhances the Breadth Of The Covishield Tm ...mentioning
confidence: 70%
“…First, the number of doses that a person can be administered was either one or two. Two doses of the vaccine have been reported to elicit higher antibody levels compared to one dose [ 7 , 16 , 17 ]. Second, the number of days between the last vaccination date and the date of sample collection has been found to be an indicator of the increasing or decreasing trend of Anti-S and Anti-NC levels.…”
Section: Methodsmentioning
confidence: 99%
“…To address this gap, we developed a hybrid machine learning approach based on serological indicators to anti-NC and anti-S along with other parameters such as prior history of infection (for Covaxin recepients whose serology history was available), days since last vaccination, gender, age and number of doses taken, as these may have an impact on assessing the infection status of an individual [ 16 , 17 ]. Machine learning (ML) based approaches have shown the ability to integrate multiple parameters to provide a holistic impression of the output variable [ 18 ].…”
Section: Introductionmentioning
confidence: 99%